Separação espacial de fases no modelo de seis vértices - Passos, Ingryd Rodrigues dos (2020)
In this work, we have studied the six-vertex model with domain wall and reflecting end boundary conditions, focusing mainly on the influence of boundary conditions on the thermodynamic limit. In order to find a complete analytical description for the so-called arctic curves, we have investigated three types of boundary correlations. These correlations were later used in two different methods designed to find the curves.